2015
DOI: 10.1039/c5nj00167f
|View full text |Cite
|
Sign up to set email alerts
|

Structure and ionization of sulfuric acid in water

Abstract: Newly recorded Raman spectra of aqueous sulfuric acid provide scattering shifts of very high sensitivity hence signal-to-noise ratios, at a broad concentration range, up to 17 M. I interpret the spectra as (a) providing no evidence for incomplete H 2 SO 4 ionization at low concentration, (b) reflecting only one dissociation event below B5 M, (c) indicating a gradual ion association at B5-12.5 M, and (d) exhibiting further structural changes of the sulfate above 12.5 M. The analysis of the Raman shifts supports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…[38][39][40][41] In addition to the low-frequency Raman lines of the H 2 SO 4 , HSO 4 − , and SO 4 2− ions in the 100-to1,800-cm −1 region, it is characterized by a strong and broad OH band (2,500-3,500 cm −1 ), which is assigned to the contributions from the ν 1 stretching mode of hydrated H 3 O + ions and H 2 O molecules. [42] In a recent Raman study, Fraenkel [43] suggested the existence of H 4 SO 5 (para-sulfuric acid) in the concentration range of~5.0 to 12.5 M H 2 SO 4 . This conclusion was supported by the absence of one O═S═O vibrational band at 1,150 cm −1 , which is a characteristic of H 2 SO 4 .…”
Section: Sulfuric Acidmentioning
confidence: 99%
“…[38][39][40][41] In addition to the low-frequency Raman lines of the H 2 SO 4 , HSO 4 − , and SO 4 2− ions in the 100-to1,800-cm −1 region, it is characterized by a strong and broad OH band (2,500-3,500 cm −1 ), which is assigned to the contributions from the ν 1 stretching mode of hydrated H 3 O + ions and H 2 O molecules. [42] In a recent Raman study, Fraenkel [43] suggested the existence of H 4 SO 5 (para-sulfuric acid) in the concentration range of~5.0 to 12.5 M H 2 SO 4 . This conclusion was supported by the absence of one O═S═O vibrational band at 1,150 cm −1 , which is a characteristic of H 2 SO 4 .…”
Section: Sulfuric Acidmentioning
confidence: 99%
“…The characteristics of these two ions are interrelated so that they can reduce the metal content in silica. (Fraenkel, 2015). The reactions that occur in metal oxides can be seen in these following equations:…”
Section: Preparation Of Silica Purificationmentioning
confidence: 99%
“…In most cases, the dissociation of strong mineral acids is investigated for fundamental research on species interaction and thermodynamic parameters. 2226 H-bond formation, hydration number, and dissociation of carboxylic acids have been investigated by factor analysis and IR spectroscopy in combination with titration and selective water spectra subtraction for quantitative calibration. 2729 The approach has been suggested for Raman spectroscopy but has not yet been realized.…”
Section: Introductionmentioning
confidence: 99%